Golden — Heaven’s Doors in Christian Temples - Андрејић, Живојин (Sabornost - The Theological Year-book, 2016)
The door of a temple marks the border between the secular and profane. The front doors to the Christian temples are sacred pilgrimage passes leading to the shrines of sanctuaries, to the places of the true presence of the deity. Consequently, a temple itself is a sort of a door. ’The Holy Door’ reminds of a passage from sin to grace and of reaching the Paradise on the Doomsday. Thus, a Holy Door is a Heavenly Door at the same time. It is the entrance to the heavenly Jerusalem, the Golden Gate. Conversely, a truly golden — gilded door into a Christian church converts a temple into Paradise. The most significant contemporary role models for making the golden door in Resava monastery can be found in Istanbul, Venice and Florence.The authentic looks of the door entrance to the nave of the church of St. Trinity in Resava is shown on the model of the temple held by despot Stefan in his founder’s ensemble. The door is painted the golden color like the despot’s pieces of clothing, also of gold — gold embroidery. This is a solid proof that, whether they were wooden or bronze, the door to the church in Resava used to be plated — Golden Gate. Having analyzed the looks of other great foundations built by Serbian royalty, we have concluded that the “Golden Gates” were also present in the churches in monasteries such as Ravanica, Lesnovo, Treskavac, Matejca, Psaca, Gracanica, Hilandar, Mileseva, Zica and Studenica.